Regional Gray Matter Atrophy Coexistent with Occipital Periventricular White Matter Hyper Intensities - Dazhi Duan; Congyang Li; Lin Shen; Chun Cui; Tongsheng Shu; Jian Zheng (Frontiers in Aging Neuroscience, 2016)
White matter hyperintensities (WMHs) and brain atrophy often coexist in the elderly. Additionally, WMH is often observed as occipital periventricular hyperintensities (OPVHs) with low-grade periventricular white matter lesions and is usually confined within an anatomical structure. However, the effects of OPVHs on gray matter atrophy remain largely unknown. In this study, we investigated gray matter atrophy in OPVHs patients and explored the relationship between such atrophy and clinical risk factors. T1-weighted and T2-weighted MRI were acquired, and voxel-based morphometry (VBM) analysis was applied. The clinical (demographic and cardiovascular) risk factors of the OPVHs patients and healthy controls were then compared. Lastly, scatter plots and correlation analysis were applied to explore the relationship between the MRI results and clinical risk factors in the OPVHs patients. OPVHs patients had significantly reduced gray matter in the right supramarginal gyrus, right angular gyrus, right middle temporal gyrus, right anterior cingulum and left insula compared to healthy controls. Additionally, OPVHs patients had gray matter atrophy in the left precentral gyrus and left insula cortex, and such atrophy is associated with a reduction in low-density lipoprotein cholesterol and apolipoprotein-B.